Integrating family and friend support, information technology, and diabetes education in community-centric diabetes self-management. (8th November 2020) - Higa, Christina; Davidson, Elizabeth J; Loos, Joanne R
Abstract: Objective: Diabetes self-management (DSM) education, social support, and information technology interventions can improve patient engagement and health. A major challenge is animating, integrating, and accessing resources in under-resourced, rural communities. Set in an island community in Hawai'i, this study piloted a program that integrated friend-and-family support, community health services, telehealth-enabled DSM education, and mobile technologies by activating the community's social capital to support the program. Materials and Methods: An action research approach informed the design and implementation of a community-based DSM program that included: friends and family support, telehealth classes, personalized consultations, Bluetooth-enabled blood glucose monitors, and text messaging support. Outcomes were evaluated using biometric data, surveys, interviews, and participant observations. Results: The study spanned 9 months with 7 dyads, each with 1 individual with type 2 diabetes and a friend or family member. Six of the 7 participants with diabetes experienced reduced hemoglobin A1c percentages, with 3 reducing by more than 1%. The seventh participant maintained a hemoglobin A1c level within American Diabetes Association recommended ranges. DSM knowledge and self-care behaviors improved overall. Interviews and participant observations highlighted program strengths and social challenges associated with the interpersonal relationships between the members of the dyads. Conclusions: A community-centric diabetes program can enhance understanding of diabetes etiology, DSM activities, and communication skills for effective disease management support in under-resourced rural communities. Social capital among community members, leveraged with health information technology, can catalyze and integrate limited health system resources for DSM and social support as a cost-effective strategy to develop community-centric chronic healthcare management initiatives.